Molecular characteristics and temperature tolerance function of the transient receptor potential in the native Bemisia tabaci AsiaII3 cryptic species - Shun-xia JI; Xiao-na SHEN; Lin LIANG; Xiao-di WANG; Wan-xue LIU; Fang-hao WAN; Zhi-chuang LÜ (Journal of Integrative Agriculture, 2020)
Insects are poikilothermic animals, and temperature is one of the most important abiotic factors affecting their spread and distribution. For example, differences in thermal tolerance may underlie the significant differences in geographical distributions between the native AsiaII3 and invasive MED (Mediterranean) cryptic Bemisia tabaci species in China. Transient receptor potential (TRP) channels are key components of the insect temperature perception system and act as molecular thermometers since they can be activated by specific changes in temperature. In this study, we cloned and characterized the AsiaII3 BtTRP gene and revealed its functions in the response to thermal stress. The full-length cDNA of BtTRP was 3821 bp, with a 3501-bp open reading frame encoding a 132.05-kDa protein. Comparing the deduced amino acid sequences of AsiaII3 BtTRP and MED TRP revealed five amino acid differences. In situ hybridization indicated that BtTRP might be widely expressed throughout the AsiaII3 adult body. BtTRP mRNA expression reached the highest levels after exposure to mild thermal stimuli (12 and 35°C), showing that BtTRP expression can be induced by temperature stress. Furthermore, the thermal tolerance of AsiaII3 after BtTRP dsRNA feeding was significantly lower than that of the control. Taken together, the present study highlights the importance of TRP channels for B. tabaci thermal resistance, and allows us to infer that the differences in amino acids between AsiaII3 and MED might cause the differences in thermal tolerance of these two cryptic species. This study provides a new direction for investigating geographic distribution differences between invasive and native insects.